2007
DOI: 10.1007/s11199-007-9242-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Attitudes and Careers: A Longitudinal Study

Abstract: Data from the Monitoring the Future Study were used to examine the impact of early gender role attitudes on later career outcomes for women and men. We also examined the impact of marriage, children, and labor market outcomes on changes in gender role attitudes. Women's early gender role attitudes predicted their later work hours and earnings. Women's work hours predicted their later gender egalitarianism. Children were negatively associated with later gender egalitarianism for both women and men. Findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
181
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(196 citation statements)
references
References 42 publications
(58 reference statements)
9
181
1
5
Order By: Relevance
“…Empirical studies that have examined the causal relationships between gender role attitudes and later labour market behaviour found evidence for an effect of early gender role attitudes on later labour market outcomes (Cunningham 2008) but also of labour market behaviour on later gender role attitudes (Corrigall and Konrad 2007;Kroska and Elman 2009). However, theoretically sound arguments exist for causation in both directions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Empirical studies that have examined the causal relationships between gender role attitudes and later labour market behaviour found evidence for an effect of early gender role attitudes on later labour market outcomes (Cunningham 2008) but also of labour market behaviour on later gender role attitudes (Corrigall and Konrad 2007;Kroska and Elman 2009). However, theoretically sound arguments exist for causation in both directions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is built upon both stereotypically masculine traits called agency (such as ''decisive,'' ''active'') and stereotypically feminine traits called communion (such as ''empathic,'' ''warm''). It has been shown that agency is especially important in predicting career-related behavior (Abele, 2003;Corrigall & Konrad, 2007;Kirchmeyer, 1998) whereas communion has an impact on social functioning (e.g., Feldman & Aschenbrenner, 1983;Kasen, Chen, Sneed, Crawford, & Cohen, 2006;Uchronski, 2008).…”
Section: Present Researchmentioning
confidence: 99%
“…For example, extrafamilial experiences such as independent living , higher levels of educational attainment Davis 2007), and contexts related working outside the home (e.g., full-time employment: Davis 2007; increased work hours: Corrigall and Konrad 2007) have been related to more egalitarian attitudes.…”
Section: Emerging Evidence Of Gender Role Attitude Malleabilitymentioning
confidence: 99%